Strategi Pengembangan Sumber Daya Manusia (SDM) Berbasis Kearifan Lokal pada Koperasi Desa (Kopdes) Merah Putih di Kabupaten Labuhanbatu - Dewi Ratna Bulan Siregar (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to formulate a human resource development strategy based on local wisdom at Koperasi Desa (Kopdes) Merah Putih in Labuhanbatu Regency. The study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving 15 informants using purposive sampling consisting of cooperative managers, members, community leaders, and village government officials. Data were analyzed using an interactive model, including data reduction, data display, and conclusion drawing. The results indicate that the cooperative’s HR condition is still in a developing stage, characterized by limited managerial competence, business planning skills, and financial literacy, despite relatively high member participation. The identified local wisdom values include mutual cooperation, deliberation, and a sense of kinship, which function as social capital in cooperative management. A human resource development strategy based on local wisdom has the potential to enhance the effectiveness, independence, and sustainability of village cooperatives through a contextual and participatory approach. Future research is recommended to test this strategy across various cooperative contexts and examine its quantitative impact on cooperative performance.